A Fast De Couple Method As Power Flow Optimization In Cooking Oil Processing Factory Based Matlab - Haris Gunawan (Sean Institute, 2024)
Power losses that occur in transmission lines result in various impacts that arise, including a decrease in voltage on the transmission line, low power factor that occurs. To reduce the occurrence of power losses that occur in transmission lines, capacitors are installed. In installing capacitors, attention must be paid to the channels that use them, the location of the capacitor and the size of the capacitor used. This is done so that the placement of the capacitor can be optimal in reducing the power losses that occur.This analysis is applied using the fast de-coupling method on a 20 kV power system.with applicationMatlab 7.0, after analysisknowntotal P loss – loss = 76,025 kW, and Q loss = 216,077 kVAR. After optimization by adding a capacitor to bus 2, it was found that the power losses were smaller, namely total P loss – loss = 46,438 kW and Q loss = 125,307 kVAR.